Cancer patients’ experiences of error and consequences during diagnosis and treatment - Henriette Lipczak (The Beryl Institute, 2015)
The study objective was to investigate patient experienced error during diagnosis and treatment of cancer. The design included a nationwide patient survey on quality and safety in Danish cancer care. Responses regarding patient experienced error were separately analyzed, quantitative responses using descriptive statistics and qualitative responses using systematic text analysis. Study participants included 6,720 adult patients with a first time diagnosis of cancer registered between May 1st and August 31st 2010. The patients received a questionnaire concerning their experiences of care received by general practitioners, specialist practitioners and at the hospital. A response rate of 65% was achieved. 10 – 25% of patients experienced error during diagnosis or treatment. 61% reported that hospital errors had consequences. Unexpected surgical errors/complications (27%), delay due to doctors’ assessment errors (24%) and unavailable test results (21%) were the most frequent types of errors identified using closed questions. 819 qualitative responses supplemented this information and revealed errors related to cancer detection, planning & coordination, patient-provider communication, administrative processes and treatment & medication. Physical, psychological, social as well as organizational consequences of the errors were uncovered. Patient experiences of errors suggest that practices related to informed consent, diagnostic reasoning as well as handling of test results, referrals and the medical chart should be further improved. In addition, safety aspects of the patient-provider communication and involvement of patients as an extra safety barrier merit further study.